Motion Graphic Animation Video as Alternative Learning Media - Amali, Lanto Ningrayati; Zees, Nurtianingrat; Suhada, Sitti (Universitas Negeri Gorontalo, 2020)
Lack of students' attention and interest to learn influence the learning process within the class. Thus, their learning achievement decreased. This study aims at designing a motion graphic, video animation learning media in Indonesian history subject. This study uses a research and development method based on the modified research model developed by Borg and Gall with five stages model namely, needs analysis, media design, product development, evaluation and product trial, and final product. This study reveals that the average pretest score before the implementation of the learning media is 57.60, whereas the average posttest score after the motion graphic, animation video learning media implementation is 79.20. The fitness of the media feedback from the media experts' score is 88% with very appropriate criteria. Also, the material expert gives a score of 89% for the media appropriateness with very appropriate criteria, and users' (students) feedback on the media is 87.9% with very appropriate criteria. It is concluded that the designed motion graphic, animation video learning media for Indonesian history subject positively influences students' learning achievement and is appropriate to be applied in Indonesian history subjects.